Penerapan Metode Fuzzy Tsukamoto Untuk Memprediksi Kebutuhan Praproduksi Pengolahan Tempe - Nugroho, Fifto; Putri Yusup, Anissa Al Fatika; Awul, Maria Fatima; Babys, Rosa Angelina (Forum Kerjasama Pendidikan Tinggi, 2023)
As a staple food in Indonesia, people from various socio-economic backgrounds enjoy tempeh. Due to the popularity of tempeh and its low price, its health benefits have been widely recognized. Tempe production is still dominated by home-based businesses. Due to the ever-increasing demand, the Jakasampurna tempeh entrepreneurs, in the West Bekasi region, must balance the efficient production rate by maintaining the best quality of tempeh. The impact that occurs during pre-production related to the purchase of raw materials for making tempeh causes a lack of availability of basic ingredients for tempeh, even the difference is too large, the risk of ingredients being wasted. The research is intended to help micro business tempeh producers gain efficiency when processing tempeh, by offering management and production advice based on the valid data provided. This study uses a fuzzy inference system based on the Tsukamoto technique. In-depth conversations and direct observations at the tempe factory, provide sources of information data for calculations. This study examines the role of three (3) variables-demand (X), supply (Y), and output (Z)-in the processing and production of tempeh (Z). In a situation where the value of X (demand) and Y (supply) is uncertain, and Z (output) can go up or down, this means that the three variables give results where the uncertainty is not considerable enough. The results on the fuzzy set go up and down at stock (Y). Production (Z) consists of many and few fuzzy groups. The predicted amount of tempeh output, if it is known from the data with a demand of 1595 and an existing stock of 85, then a total of 1770 will be produced, thus the production rate becomes efficient by continuing to follow the recommended production amount, then there is little risk of accumulation of basic material storage because what is used is according to demand and the use of soy-based ingredients is always fresh.